2023
DOI: 10.1111/cpr.13548
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate kinase M2 regulates kidney fibrosis through pericyte glycolysis during the progression from acute kidney injury to chronic kidney disease

Yulan Chen,
Xueyuan Bai,
Jianwen Chen
et al.

Abstract: We aimed to investigate the role of renal pericyte pyruvate kinase M2 (PKM2) in the progression of acute kidney injury (AKI) to chronic kidney disease (CKD). The role of PKM2 in renal pericyte‐myofibroblast transdifferentiation was investigated in an AKI‐CKD mouse model. Platelet growth factor receptor beta (PDGFRβ)‐iCreERT2; tdTomato mice were used for renal pericyte tracing. Western blotting and immunofluorescence staining were used to examine protein expression. An 5‐ethynyl‐2′‐deoxyuridine assay was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…PKM1 are predominantly expressed in muscle, mature spermatozoa and central nervous system, while PKM2 is expressed in brain, kidney, lung and spleen ( Alquraishi et al, 2019 ; Puckett et al, 2021 ). PKM2 is the dominant form of PK in kidney tissue ( Alquraishi et al, 2019 ), and a lot of researches have revealed that regulating PKM2 affects kidney disease progression and treatment ( Li et al, 2020a ; Chen et al, 2023 ; Xie et al, 2023 ), highlighting the important role of PKM2 in kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…PKM1 are predominantly expressed in muscle, mature spermatozoa and central nervous system, while PKM2 is expressed in brain, kidney, lung and spleen ( Alquraishi et al, 2019 ; Puckett et al, 2021 ). PKM2 is the dominant form of PK in kidney tissue ( Alquraishi et al, 2019 ), and a lot of researches have revealed that regulating PKM2 affects kidney disease progression and treatment ( Li et al, 2020a ; Chen et al, 2023 ; Xie et al, 2023 ), highlighting the important role of PKM2 in kidney disease.…”
Section: Introductionmentioning
confidence: 99%